Acute mixed-lineage leukemia treated with desensitization therapy prior to HLA–haploidentical transplantation with high donor-specific antibodies - Katsuki, Kengo; Tachibana, Takayoshi; Izumi, Akihiko; Kim, Kumryo; Suzuki, Taisei; Tanaka, Masatsugu; Nakajima, Hideaki (International journal of hematology, 2024)
A 43-year-old woman was referred to our department for hematopoietic stem cell transplantation for acute myeloid leukemia, as she failed to achieve remission following induction therapy. Umbilical cord blood transplantation was initially planned; however, multiple anti-human leukocyte antigen (HLA) antibodies with a mean fluorescence intensity of over 10,000 were detected, and optimal umbilical cord blood could not be obtained. The plan was then switched to peripheral blood stem cell transplantation (PBSCT) from the patient’s son, who had a 5/8 HLA haploidentical match. However, the patient had donor-specific antibodies against the donor’s HLA-B 0702 and HLA-C 0702. To address this issue, after rituximab therapy, the patient was given platelet transfusions from B0702- and C0702-positive donors on day − 1 and day 0, and immunoglobulin on day 0, followed by PBSCT. Donor-specific antibodies decreased by over 90%, and engraftment was confirmed on day 13. Since then, the patient has remained relapse-free and healthy. This case suggests that appropriate management of donor-specific antibodies can enable safe transplantation, even in donors who test positive for these antibodies.